Les études de Sergio Cigada, jalons incontournables de la critique flaubertienne - Liana Nissim (Flaubert: Revue Critique et Génétique)
Sergio Cigada (1933-2010) was certainly one of the greatest Italian specialists of Flaubert. In this study we will review all of Cigada’s writings (since 1956) devoted to Flaubert’s works, by highlighting for each one the pioneering criticism and proposing a rereading of his most significant studies: « Uno scritto autobiografico di Flaubert : Quidquid volueris » (1956), Un decennio di critica flaubertiana (1945-1955) (1957) and Genesi e struttura tematica di Emma Bovary (1960), a magnificent book which even today presents among the most enlightening pages of the genesis of the character Emma and her psychological make-up. But we will focus above all on Cigada’s masterpiece Il pensiero estetico di Gustave Flaubert (1964). As it is a founding work that, for the first time in the history of Flaubertian criticism, achieves a global study of Flaubert’s aesthetics exhibiting both a powerful unity and a detailed and comprehensive expression. Sergio Cigada’s dazzling insight, the clarity of his expression and the critical accuracy of his thought, all make of his essays crucial milestones for all those interested in Gustave Flaubert.